Synthesis and Antimicrobial Evaluation of Some New Thiazolo[4,5-d] pyrimidines - Balkan, Ayla; Urgun, Hüsne; Özalp, Meral (Arzneimittelforschung, 2001)
In this study, by starting from ethyl 4-amino-2,3-dihydro-3-methyl-2-thio-xothiazole-5-carboxylate (1), the compounds having 2,3-dihydro-3-methyl-5-mercapto-6-methyl/ethyl-2-thioxothiazolo[4,5-d]pyrimidin-7(6H)-one (2a, 2b) structure and their 5-(4’-nonsubstituted/-substitutedbenzoylmethyl)thio derivatives (3a-h) were synthesized. The chemical structures of the compounds were proved by IR, 1H-NMR and elemental analysis data. In vitro antimicrobial activities of the synthesized compounds were investigated against some bacteria and yeasts using the microdilution method. In view of the antimicrobial activity results, a significant inhibitory effect was observed only for compound 2a against Gram-positive bacteria and yeasts, whereas the other compounds had no remarkable activity against the tested microorganisms.
Keywords: 2-Thioxothiazolo[4,5-d]pyrimidin-7(6H)-ones, anti-bacterial activity, anti-yeast activity; in vitro studies, synthesis